Método de baixo custo para reutilização de máscaras N95 através de recarga eletrostática - Lorenzoni, Pedro Ravalha (2023)
Due to the Covid-19 pandemic, a disease caused by the Sars-CoV-2 virus, the use of personal protective masks has increased dramatically. The World Health Organization (WHO) recommends the PFF2 model, equivalent to the North American N95 respirator standard. Unlike cloth and surgical masks, whose main function is to prevent the spread of exhaled air from an infected person, thus reducing the chances of virus transmission, PFF2 masks are considered personal protective equipment (PPE) and filter up to 95% of contaminating particles [1]. One of the main characteristics of this mask is the electrostatic treatment of the innermost second layer, where a potential difference is established, acting as an electrostatic barrier and trapping particles carrying the virus [2]. However, this protection is time-limited as the mask can become damp or dirty, reducing the electrostatic barrier and, consequently, its efficiency. Therefore, this study aims to apply methods to re-electrify the mask, restoring its electrostatic protection in order to prolong its lifespan and promote reusability. Among the methods used, the following are highlighted: 1) Electrification through discharges generated by a static neutralizing gun (Zerostat); 2) Electrification through friction with nylon and polytetrafluoroethylene (PTFE). Through electrostatic mapping of the PFF2 mask using the Kelvin method and measuring the charge quantity using a Faraday cup, it was observed that the electrostatic barrier can be restored even after mask washing, and based on this, it was found that its efficiency surpasses that of new masks.